Macroprolactinoma in a Patient With Schizophrenia: A Therapeutic Challenge - Voelz, Eduardo (J Endocr Soc, 2021)
Introduction: The most common pituitary tumors are prolactinomas and they are treated with dopamine agonists. In schizophrenia, antipsychotics (dopamine receptor blockers) are used, which can result in hyperprolactinemia. The association of Schizophrenia and prolactinoma represents a clinical challenge, once the treatment of one disease can exacerbate the symptoms of the other. Clinical Case: A 39-year-old man diagnosed with schizophrenia about 20 years ago, sought medical attention in January 2015, due to frequent headache that worsened in the last 3 years and loss of visual field, with bitemporal hemianopsia. The MRI revealed a pituitary macroadenoma (22x15x27mm) with cavernous sinus invasion and displacement of the optic chiasm. In laboratory tests, the serum prolactin level was 223 ng/ml (reference value up to 20 ng/ml in men), while the others pituitary hormones were normal. Therefore, diagnosed with macroprolactinoma. Surgical resection was suggested, but due to the risks, it was decided to start drug treatment. As an initial treatment, the use of 1 mg/ week cabergoline was chosen. Four months after the first visit, prolactin remained high (203 ng/ml) and the dose was readjusted to 1.5 mg/week. In September, there was a reduction in prolactin (97 ng/ml) and a further increase (2.5 mg/week). Ten months after the first medical appointment, a new MRI was performed with a reduction of the macroadenoma (15x08x16mm), without compression of adjacent structures and prolactin of 68.5 ng/ml. In 2016, the patient had episodes of hallucination and depression, quetiapine 100 mg/day was started and his prolactin was 49,2. In February of the following year, he presented an increase in prolactin (203 ng/ml), due to the possible action of quetiapine and haloperidol parenterally 15/15 days, associated with the irregular use of cabergoline. There was no increase in volume in the MRI. In September, he presented a reduction in prolactin (65.76 ng/ml) and it was chosen to maintain the dosage of cabergoline (2.5 mg/week), injectable haloperidol in 15-15 days and quetiapine 200 mg/day. In 2018, there was an increase in prolactin (200 ng/ml), possibly linked to the increase in doses of antipsychotics. At this time the MRI has not been performed due to financial problems. The following year, MRI showed no progression of the macroadenoma. In 2020, the patient presented central hypothyroidism, (TSH: 1.2 mU/L and free T4: 0.44 ng/dl), starting Levothyroxine 50 mcg. The prolactin was 104 ng/ml in this year. Conclusion: It is necessary to analyze prolactin levels, imaging tests and the prescription of antipsychotic medications for correct analysis and evaluation of prolactinomas in schizophrenic patients.